Association of Postmenopausal Bleeding with Endometrial Carcinoma - Safia Perveen, Muhammad Suleman Azhar, Fatima Shah, Fizza Mahmood, Usama Mahmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find the association of postmenopausal bleeding with endometrial carcinoma. Study design: Cross-sectional analytical study Place and duration of study: Department of Obstetrics & Gynaecology, Sahiwal Teaching Hospital and Medical College, Sahiwal from 1st January 2019 to 31 December 2021. Methodology: One hundred women suffering from post-menopausal bleeding were enrolled. An endometrial biopsy was used for removing a piece of the tissue from the inner lining of the uterus and was conducted in suspicious women for confirming endometrial carcinoma by microscopic histopathological reporting.The frequency of endometrial carcinoma in post-menopausal women was analyzed. Results: The mean age was 56.2+0.5 years. The recurrent bleeding was observed in 7% cases and obesity was seen in 50 cases. Transvaginal ultrasonography was performed on women due to high suspicions. Out of the total 8 cases, 87.5% had a uterine thickness >5mm with no history of hormone replacement therapy. Incidence of endometrial carcinoma was 7% among postmenopausal women. Conclusion: Postmenopausal bleeding was commonly observed in obese women and in those who were on hormonal replacement therapy. Incidence of endometrial carcinoma was 7% in postmenopausal bleeding females.